PEMBELAJARAN TEMATIK DALAM MENGEMBANGKAN SIKAP TOLERANSI PADA ANAK USIA 5-6 TAHUN DI TK BRUDER KANISIUS PONTIANAK - Mirnawati, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract then aim of this research as the habitual to describe tolerance,leson plan and abstacales in develoving the habitual tolerance to 5-6 years old studens of TK Bruder Kanisius Siantan Tengah. The reseach used descriptive reseach methodology which in from qualitative approach,the sample of this reseach was group B2 studets.The resultsef were gathered from lesson of PERMENDIKNAS Tahun 2009 whereas adapted with national curriculum,habitual method ,studt tour and media were the menthod that were used to develop the students tolerance.The behavior of students of group B2 in habitual tolerance were showed from the ability ef the students to respect the diversty at school and the children were alse taught to share and cooperate and respect their friends,parents and teacherKeyword : thematic learning,tolerance